Influences of mountain closure on community composition of ecological service forest in Fuyang, Hangzhou, China - ZHANG Jun; XU Shenghua; WU Chuping; JIAO Jiejie; HUANG Yujie; GAO Hongdi; SHEN Aihua; YUAN Weigao; ZHU Jinru; GAO Zhihui; JIANG Bo (浙江大学学报. 农业与生命科学版)
According to basic characteristics (e. g., distribution pattern, forest type) of the ecological service forest in Fuyan, Hangzhou, China, we aimed to understand the changes in community composition, stand quality, and secondary succession process after the mountain closure. Using the method of forest field observation, experimental analysis, mathematical and statistical analysis, we established 88 permanent monitoring sampling plots to track forest community factors periodically.Our results showed that the forest quality of Fuyang ecological service forest improved significantly between 2009 and 2014. Specifically, the stem density of young broadleaved forest increased by 325.00 individual/hm2(27.4%, P<0.01), its average diameter at breast height increased by 0.65 cm (8.2%, P<0.05), and its community biomass increased by 4.53 t/hm2 (5.7%). The average diameter at breast height of middle-aged broadleaved forest increased by 0.23 cm (2.1%) and its community biomass increased by 18.55 t/hm2(15.9%, P<0.01). The stem density of coniferous and broadleaved mixed forest at three age classes increased slightly during the past five years. The diameter at breast height of young coniferous and broadleaved mixed forest increased the largest by 1.07 cm (12.8%), and its community biomass increased by 20.59 t/hm2(20.7%, P<0.01). The community biomass of middle-aged coniferous and broadleaved mixed forest also increased by 12.14 t/hm2(11.5%, P<0.01). Comparing the age structure of Fuyang ecological service forest between 2009 and 2014, the areas of young forest and middle-aged forest reduced, while the areas of premature forest and mature forest increased. The area of young broadleaved forest did not change significantly and the middle-aged forest gradually turned into premature forest. Meanwhile, the area of young coniferous and broadleaved mixed forest decreased, while the area of middle-aged forest and premature forest increased. Our results showed that coniferous and broadleaved mixed forest gradually changed into the middle-aged forest at young stage and into the premature forest at middle-aged stage. After five years of mountain closure of the ecological service forest in Fuyang, the proportions of broadleaved tree species in coniferous and broadleaved mixed forest and broadleaved forest increased. In the coniferous forest, the relatively dominant Cupressus funebris and Dalbergia hupeana experienced the largest increase. In the broadleaved forest, the relatively dominant Schima crenata, Celtis sinensis and Euscaphis japonica had the largest increase, while Choerospondias axillaris, Ligustrum lucidum and Pinus massoniana showed the largest decline. In the coniferous and broadleaved mixed forest, the relatively dominant Cinnamomum camphora, Sassafras tzumu, Schima crenata experienced the largest increase, while Castanopsis sclerophylla, Cupressus funebris, and Euscaphis japonica displayed the largest decline.Our findings suggest that for abundant broadleaved tree species resources at renewal layers, the mountain closure is an effective measure to accelerate the succession of coniferous forest to coniferous and broadleaved mixed forest, then to broadleaved forest. For forests with high canopy or few target tree species, it is necessary to take some artificial cultivation measures (e. g., artificial planting) to promote the species diversity and improve the ecological effects.